2020
DOI: 10.1590/pboci.2020.116
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene and Dental Caries Status on Systemic Lupus Erythematosus Patients: A Cross-Sectional Study

Abstract: To evaluate the oral hygiene and dental caries status on Systemic Lupus Erythematosus (SLE) patients, also it's with SLE disease activity. Material and Methods: This is a descriptive study with a cross-sectional approach. The study was conducted on 93 SLE patients from 2017 to 2019 on Saiful Anwar Hospital Indonesia. All SLE patients had clinical examination using DMF-T, Personal Hygiene Performance-Modified (PHP-M), Calculus Index (CI), Debris Index (DI), Plaque Index (PI) and Simplified Oral Hygiene Index (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“… 24 Regarding what is related to lupus disease activity and periodontitis, some studies showed that the severity of lupus disease activity was related to poor oral hygiene and a high incidence of dental caries. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 Regarding what is related to lupus disease activity and periodontitis, some studies showed that the severity of lupus disease activity was related to poor oral hygiene and a high incidence of dental caries. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Patients previously diagnosed with lupus gradually develop joint disorders and mood changes associated with a decrease in oral hygiene, such as a decrease in brushing frequency which, in turn, leads to an increase in periodontal disorders. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, salivary pH and flow were significantly reduced and high counts of S.mutans were noted [ 84 ]. Another study showed relationship between compromised biofilm control, SLE severity and dental caries [ 85 ]. These results raise the possibility of SLE being coincidental in the direct relationship between poor oral hygiene and dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Salah satu cara mengukur index plak adalah dengan menggunakan metode PHP-M (Personal Hygiene Performance-Modified) (Gofur et al, 2020). Frekuensi menyikat gigi yang baik adalah maksimal tiga kali sehari, yaitu setelah sarapan, setelah makan siang, dan malam saat sebelum tidur, atau minimal dua kali sehari yaitu setelah sarapan pagi dan malam sebelum tidur (Imran et al, 2022).…”
Section: Pendahuluanunclassified